Upaya Guru dalam Mengembangkan Nilai Agama dan Moral Anak Usia Dini melalui Kegiatan Keagamaan - Al Hidayah, Ukhti; Mulyani, Novi (Jurnal Pendidikan Agama Islam, 2025)
Children, as the future leaders of the nation, need to be equipped with an education that fosters good character and noble morals. Character development can be achieved through the instilling of religious and moral values. Religious activities are considered effective in supporting this process. At Al Irsyad Gintungreja Islamic Kindergarten, teachers strive to develop children's religious and moral values through daily activities such as private Quran recitation, congregational Dhuha and Dhuhur prayers, prayers before and after learning, memorising the Beautiful Names of Allah with movements, daily prayers, hadiths, short surahs, wudu practice, and Arabic vocabulary. This study aims to identify the efforts made by teachers in developing these values, using a descriptive qualitative method with observation, interviews, and documentation techniques. Data analysis was conducted through reduction, presentation, and verification, and data validity was checked through triangulation. The results of the study indicate that the Al Irsyad Gintungreja Islamic Kindergarten has successfully developed the religious and moral values of its students, as evidenced by assessment results that meet the standards.